Pharmacometric Analysis of Intranasal and Intravenous Nalbuphine to Optimize Pain Management in Infants - Pfiffner, Miriam; Berger-Olah, Eva; Vonbach, Priska; Pfister, Marc; Gotta, Verena (Frontiers in Pediatrics, 2022)
Objectives: The objective of this pharmacometric (PMX) study was to (i) characterize population pharmacokinetics (PPK) and exposure-pain response associations following intranasal (0.1 mg/kg) or intravenous (IV, 0.05 mg/kg) administration of nalbuphine, with the goal to (ii) evaluate strategies for optimized dosing and timing of painful interventions in infants 1-3 months old. Methods: PPK analysis of nalbuphine serum concentrations, prospectively collected 15, 30, and between 120-180 min post-dose, utilizing the software package Monolix. The final PPK model was applied to derive individual time-matched concentration predictions for each pain assessment (Neonatal Infant Pain Score, NIPS) after establishment of venous access and urinary catheterization or lumbar puncture. Drug exposure-pain response simulations were performed to evaluate potential benefits of higher doses with respect to a previously proposed target concentration of 12 mcg/L (efficacy threshold)(1). Results: 38 of 52 study subjects receiving nalbuphine had at least one concentration measurement and were included in the pharmacometric analysis. A two-compartment model with allometric scaling was applied to describe population PK data, with intranasal bioavailability estimated to be 41% (95%CI: 26-56%). Model-based simulations showed that the proposed efficacy threshold (12 mcg/L) is expected to be exceeded with an IV dose of 0.05 mg/kg for 6 min, with 0.1 mg/kg for 30 min and with 0.2 mg/kg for 80 min. This efficacy threshold is not achieved with intranasal doses of 0.1 and 0.2 mg/kg, whereas an intranasal dose of 0.4 mg/kg is expected to exceed such threshold for 30 to 100 min. Conclusion: This PMX study confirmed that bioavailability of intranasal nalbuphine is close to 50%. Exposure-pain response simulations indicated that an intranasal dose of 0.4 mg/kg is required to provide a comparable pain control as achieved with an IV dose of 0.1- 0.2 mg/kg. The optimal time window for painful procedures appears to be within the first 30 min after IV administration of 0.1 mg/kg nalbuphine, whereas such procedures should be scheduled 30 min after an intranasal dose of 0.4 mg/kg nalbuphine. Additional clinical studies are warranted to confirm these PMX based recommendations and to further optimize pain management in this vulnerable infant population.